A comparison of root canal preparations using stainless steel, Ni-Ti hand, and Ni-Ti engine-driven endodontic instruments an in vitro study - Parvathaneni, Krishna Prasad; Goel, Beena Rani; Parvathaneni, Bharani Devi (Bangladesh Journal of Medical Science, 2010)
The main advantage of nickel titanium instruments is that they permit canal preparation with less transportation and ledging. Hand used Ni-Ti and rotary Ni-Ti instruments have a wider range of elastic deformation and greater flexibility. The aim of the present study was to evaluate and compare the preparation time, loss of working length, apical transportation, instrument deformation and fracture with stainless steel, Ni-Ti hand and Ni-Ti rotary endodontic instruments. Fifty freshly extracted human mandibular molars with curved roots were collected and stored in 10% formalin. The samples were divided into 3 groups of 15 each. The access opening was made for each tooth and the biomechanical preparation was carried out using crown down pressureless technique in all the groups. Group I was instrumented with stainless steel files, group II with hand Ni-Ti and group III with Ni-Ti rotary files. The preparation time to enlarge each canal was recorded in minutes and seconds, which included only active instrumentation. Following preparation, the final length of each canal was subtracted from the original length to give the loss of working length. SEM photographs of the deformed and fractured instruments were taken. The apical transportation was measured using computer software (Microdraw 4.1). The readings were noted and statistically analyzed. The results of this in vitro study showed that the mean preparation time was less with Ni- Ti rotary (1.85 min) when compared to hand Ni-Ti (6.33) and stainless steel files (6.73), which was statistically significant. The loss of working length was more for stainless steel group which was statistically significant (P<0.05) when compared with the other 2 groups.One instrument in stainless steel and one in Ni-Ti rotary files were fractured. Only one instrument in stainless steel file deformed permanently. Apical transportation was found to be greater in stainless steel group than other groups (P<0.01) which was statistically significant. Considering the parameters in this study, Ni-Ti rotary files proved to perform better than the other two groups. Key words: Canal preparation; crown-down pressure less technique; double exposure radiographic technique. DOI: 10.3329/bjms.v9i4.6689 Bangladesh Journal of Medical Science Vol.09 No.4 July 2010 pp.223-230